And then she vanished - Jones, Nick (Ashland, OR : Blackstone Publishing, Ashland, OR, 2021)
"Still haunted by the disappearance of his little sister, Amy, over twenty years ago, Joseph Bridgeman's life has fallen apart. When a friend talks him into seeing hypnotherapist Alexia Finch to help with his insomnia, Joseph accidentally discovers he can time travel. His first trip only takes him back a few minutes, but his new-found ability gives him something he hasn't felt for the longest time: hope. Joseph sets out to travel back to the night Amy went missing and save her. But after several failed attempts, he discovers the farther back he travels, the less time he gets to stay there. And the clock is ticking. With the help of Alexia, Joseph embarks on a desperate race against the past to save his sister. Can he master his new skill and solve the mystery of Amy's disappearance before it is too late?" provided by the publisher.
Keywords: Insomniacs -- Fiction; Time travel -- Fiction; Missing persons -- Fiction; Sisters. -- Fiction